2018
DOI: 10.1186/s13041-018-0411-6
|View full text |Cite
|
Sign up to set email alerts
|

proBDNF is modified by advanced glycation end products in Alzheimer’s disease and causes neuronal apoptosis by inducing p75 neurotrophin receptor processing

Abstract: Alzheimer disease (AD) is a complex pathology related to multiple causes including oxidative stress. Brain-derived neurotrophic factor (BDNF) is a neutrotrophic factor essential for the survival and differentiation of neurons and is considered a key target in the pathophysiology of various neurodegenerative diseases, as for example AD. Contrarily to BDNF, the precursor form of BDNF (proBDNF) induces apoptosis through the specific interaction with p75 and its co-receptor, Sortilin.We used hippocampal tissue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 63 publications
2
66
0
1
Order By: Relevance
“…Many studies have demonstrated AGEs are considered as potent toxic molecules that produce several non-communicable diseases such as T2D, CRC, cardiovascular diseases, Parkinson disease, AD (63)(64)(65)(66)(67)(68). Epidemiological evidence has reported that elevated AGEs were associated with CRC (69).…”
Section: Ligands Advanced Glycation End-productsmentioning
confidence: 99%
“…Many studies have demonstrated AGEs are considered as potent toxic molecules that produce several non-communicable diseases such as T2D, CRC, cardiovascular diseases, Parkinson disease, AD (63)(64)(65)(66)(67)(68). Epidemiological evidence has reported that elevated AGEs were associated with CRC (69).…”
Section: Ligands Advanced Glycation End-productsmentioning
confidence: 99%
“…Earlier studies found significantly reduced levels of both proBDNF and BDNF in parietal cortex taken from subjects with mild cognitive impairment and mild to moderate AD compared with age‐matched controls 21 . However, recent work has reported that proBDNF levels in the hippocampus as well as CSF proBDNF/BDNF ratios were both significantly higher in AD subjects compared with age‐matched controls, and also found evidence supporting a role for proBDNF‐p75/Sortilin signalling in AD pathogenesis 47 …”
Section: Discussionmentioning
confidence: 96%
“…Although mature BDNF promotes neurogenesis and activates prosurvival signaling through tropomyosin receptor kinases (Trks) [23][24][25], its precursor proBDNF binds to the p75 neurotrophin receptor (p75NTR), a tumor necrosis factor receptor-like molecule. Activation of p75NTR by proBDNF can induce neuronal apoptosis in different conditions [26][27][28]. p75NTR is expressed widely during synaptogenesis and subsequently downregulated in the adult brain.…”
Section: Discussionmentioning
confidence: 99%